Breast‐conserving surgery versus mastectomy in young women with breast cancer in Asian settings. Issue 1 (18th October 2018) - Sinnadurai, S.; Kwong, A.; Hartman, M.; Tan, E. Y.; Bhoo‐Pathy, N. T.; Dahlui, M.; See, M. H.; Yip, C. H.; Taib, N. A.; Bhoo‐Pathy, N.
Abstract : Background: Mastectomy rates among women with early breast cancer in Asia have traditionally been high. This study assessed trends in the surgical management of young women with early‐stage breast cancer in Asian settings. Survival in women treated with breast‐conserving surgery (BCS; lumpectomy with adjuvant radiotherapy) and those undergoing mastectomy was compared. Methods: Young women (aged less than 50 years) newly diagnosed with stage I or II (T1–2 N0–1 M0) breast cancer in four hospitals in Malaysia, Singapore and Hong Kong in 1990–2012 were included. Overall survival (OS) was compared for patients treated by BCS and those who had a mastectomy. Propensity score analysis was used to account for differences in demographic, tumour and treatment characteristics between the groups. Results: Some 63·5 per cent of 3536 women underwent mastectomy. Over a 15‐year period, only a modest increase in rates of BCS was observed. Although BCS was significantly associated with favourable prognostic features, OS was not significantly different for BCS and mastectomy; the 5‐year OS rate was 94·9 (95 per cent c.i. 93·5 to 96·3) and 92·9 (91·7 to 94·1) per cent respectively. Inferences remained unchanged following propensity score analysis (hazard ratio for BCS versus mastectomy: 0·81, 95 per cent c.i. 0·64 to 1·03). Conclusion: The prevalence of young women with breast cancer treated by mastectomy remains high in Asian countries. Patients treated with BCS appear to survive as well as those undergoing mastectomy. Abstract : The mastectomy rates among young women with early‐stage breast cancer in Asian settings remain substantially higher than the reported rates in the USA and Europe. The present study findings provide reassuring evidence for young Asian women with early breast cancer that breast conservation therapy (breast‐conserving surgery with adjuvant radiotherapy) and mastectomy yield similar overall survival benefits, corroborating evidence from previous studies conducted in Western settings. No real survival difference